Cosmetic and Toiletry Formulations, Volume 3 (2nd Edition) - Flick, Ernest W. (William Andrew Publishing/Noyes, 2011)
This book contains 775 cosmetic and toiletry formulations based on information received from numerous industrial companies and other organizations.